Exploration Of Sosrokartono's Moral Teachings And Their Resonance With The Axiology Of Islamic Education - Witoyo, Nurryanto Midi; Abdi, Supriyanto (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2024)
This study aims to explore and examine the moral teachings of Raden Mas Panji Sosrokartono, an important figure in Javanese moral and spiritual tradition, and their resonance with the axiology of Islamic education. More specifically, the study examines Sosrokartono's moral teachings as reflected in his symbolic names (sinandi) such as "Sang Alif," "Mandor Kloengsoe," and "Djoko Pring," which contain deep spiritual and social values. It also looks at his wider moral teachings as contained in his Ilmu Catur Murti and Ilmu Kantong Bolong that emphasize harmony, sincerity, simplicity, and selfless devotion. This study is a library research with a historical-critical-philosophical approach. The study found that the Sosrokartono’s moral teachings strongly resonate with the axiology of Islamic education in relation to the values of faith (aqidah), worship (ibadah), morality (akhlaq), and nationalism. The study argues that Sosrokartono’s locally rooted moral teachings are highly compatible with the axiological aims of Islamic education to form individuals who are pious, have noble character, and love for their nation. Sosrokartono's holistic moral teachings, combining intellectuality, morality, spirituality, and harmonization with divine, humanistic, and cultural values, are thus very relevant to the development of Muslim personalities and national values.